Perioperative management of patient with hemophilia a underwent orthopedic surgery - Senapathi, Tjokorda GA; Gede Widnyana, I Made; Mahaalit Aribawa, I Gusti Ngurah; Ryalino, Christopher (Bali Journal of Anesthesiology, 2017)
Hemophilia presents challenging consideration for anesthesiologists. In non emergency cases it is essential that factor VIII is raised to its optimal activity prior to surgery. Intra operative bleeding is a fatal complication in hemophilia. Certain measurements must be taken under considerations to manage this case for anesthesia. Peripheral lines should be secured with utmost care. Intramuscular injections and arterial punctures must be avoided. Intubation and airway positioning should be done gently in deep plane anesthesia. Small vessels hemostatis must be taken care of by the surgeon. A multidisciplinary team has to be involved when patients with hemophilia are planned for surgery. The knowledge related to replacement therapy should be mastered not only by hematologist, but also by the whole team involved in patient management.